Web Accessibility for Developers - Open Textbook Library (Open Textbook Library, 2019)
Web Accessibility for Developers is a technical book aimed primarily at programmers. Learn how to develop accessible interactivity on the Web and gain expertise using WAI-ARIA, a W3C specification that enables optimal use of assistive technologies, like screen readers, when navigating the Web.
1. Introduction -- 2. Introduction to WAI-ARIA -- 3. Basic WAI-ARIA -- 4. Interactive WAI-ARIA (Basic) -- 5. Interactive WAI-ARIA (Intermediate) -- 6. Interactive WAI-ARIA (Advanced)
In English.
Description based on print resource
Keywords: Computer Science -- Textbooks